Initial State of Erythrocytes as Factor, Determining Their Sensibility to Hypertonic Stress. Role of PEO-1500 and Temperature - Aleksandrova, D. I.; Orlova, N. V.; Shpakova, N. M. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of PEO-1500 on resistance of human, bovine and equine erythrocytes to hypertonic shock (4.0 M NaCl) under 37 and 0Â°C was studied. It has been shown that decrease of mammalian erythrocyte volume with PEO-1500 concentration increase is accompanied by rise in cell resistance to the activity of hypertonic shock under 37 and 0Â°C.